Analisis kepatuhan wajib pajak kendaraan bermotor dan bea balik nama kendaraan bermotor dalam upaya meningkatkan penerimaan pajak daerah pada kantor UPTD-PPD Samsat Kabupaten Minahasa Tenggara - Massie, Angela Meilan; Karamoy, Herman; Walandouw, Stanley Kho (Riset Akuntansi dan Manajemen Pragmatis, 2024)
Taxpayer compliance is the obedience required for taxpayers in fulfilling their tax obligations. One of the tax obligations that must be carried out is paying motor vehicle taxes and transfer of motor vehicle tittle fee. However, there are problems that often occur so that the government is difficult to get more income from the PKB and BBNKB sectors, the purpose of this study is to analyze the compliance of motor vehicle tax and motor vehicle title transfer fees at the UPTD-PPD Samsat’s office in Southeast Minahasa Regency in 2018-2021, to find out and analyze the causes of community disobedience in paying motor vehicle tax and motor vehicle title transfer fees. The research method used is descriptive qualitative method. Based on the results of the study, it shows that the compliance in the UPTD-PPD Samsat office of Southeast Minahasa Regency is considered good. In the years 2018-2020, the realization has reached the target, but in 2021 the target was not achieved due to the presence of covid-19 which has hindered the economy of the community, and the target increase in 2021 is 40%, different from the years 2018-2020.